(untitled) (Mulheres no Discurso - Women in Discourse, 2025)
The present article investigates the relevance of addressing gender issues in the teaching of Portuguese literature, adopting a multidisciplinary theoretical framework that draws on discourse analysis, gender studies, and feminist literary theory (with particular reference to Butler, 1990; Showalter, 1977; and hooks, 1994). The main objective of this study, based on an action-research methodology, is to analyze the impact of a critical pedagogical approach on students' perceptions regarding gender stereotypes. To this end, focusing on an intervention carried out in an 8th-grade class, the study observed how the analysis of literary texts, aimed at deconstructing stereotypes, can influence gender representations and promote a more inclusiveand reflective reading. In order to assess the results of this pedagogical intervention, pre- and post-intervention questionnaires were applied, and the results were compared with those of a control group. The data seems to reveal that the pedagogical intervention fostered greater critical awareness of gender constructs, reinforcing the importance of an inclusive and critical educational approach in the school curriculum. In this sense, the article highlights the importance of educators adopting methodologies that promote the deconstruction of gender stereotypes and encourage the development of active and critical citizenship.